2005
DOI: 10.1093/ajcn/81.3.597
|View full text |Cite
|
Sign up to set email alerts
|

Validity of impedance-based equations for the prediction of total body water as measured by deuterium dilution in African women

Abstract: Background: Little information is available on the validity of simple and indirect body-composition methods in non-Western populations. Equations for predicting body composition are populationspecific, and body composition differs between blacks and whites. Objective: We tested the hypothesis that the validity of equations for predicting total body water (TBW) from bioelectrical impedance analysis measurements is likely to depend on the racial background of the group from which the equations were derived. Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…We found that height, weight, impedance, sex and age produced the most effective prediction of %FFM with an R 2 of 0.81. This closely agrees with novel equations developed for a hand-to-hand impedance system in a group of West African women (R 2 ¼ 0.82), when the manufacturer's equations were also found to be biased (Dioum et al, 2005a). In our study, the addition of skinfold thickness measurements into the final equation improved the ability even further with an adjusted R 2 of 0.84, even though fat-free tissue is not directly an output associated with skinfold thickness.…”
Section: Discussionsupporting
confidence: 82%
“…We found that height, weight, impedance, sex and age produced the most effective prediction of %FFM with an R 2 of 0.81. This closely agrees with novel equations developed for a hand-to-hand impedance system in a group of West African women (R 2 ¼ 0.82), when the manufacturer's equations were also found to be biased (Dioum et al, 2005a). In our study, the addition of skinfold thickness measurements into the final equation improved the ability even further with an adjusted R 2 of 0.84, even though fat-free tissue is not directly an output associated with skinfold thickness.…”
Section: Discussionsupporting
confidence: 82%
“…Immediately after the anthropometric exams and BIA, saliva was collected from the subjects and deuterium oxide was offered to them. This permitted the exams to be performed at the same time and under the same conditions, with a consequent constant state of hydration during all methods of body assessment used in the study (18).…”
Section: Subjectsmentioning
confidence: 99%
“…It is evident from recent studies that the use of BIA for the assessment of body composition in children requires specific prediction formulas differing from those established for adults (12)(13)(14). Such formulas have been developed for the prediction of FFM (15)(16)(17)(18)(19) and of TBW (12)(13)(14) in children. BIA could also be an easily applicable method for the assessment of body composition in obese children, but until now it has not been validated for this population.…”
mentioning
confidence: 99%
“…The inclusion of BMI in the equation indicates that it is a valuable component in body fat assessment, though on its own it may be prone to error. Though previous BIA equations too included height 2 / resistance as a prediction variable (14-16), body weight and age, which are common variables in other prediction equations (10), body weight may have been eliminated due to the inclusion of BMI into our equation and age, due to the narrow age range of our study population.…”
Section: Discussionmentioning
confidence: 99%
“…There are no published BIA equations for South Asian adolescents, with the few available equations being derived for the prediction of total body water (TBW), and through it, fat mass (7)(8)(9). Ideally, the available %FM prediction equations should be validated in the population being assessed prior to use, or population specific prediction equations should be derived against a reference method to improve accuracy of BIA analysis (10).…”
Section: Introductionmentioning
confidence: 99%